Propranolol Therapy for an Abdominal Giant Haemangioma in a Neonate - Docx, Martine Karine Francine; Vandenberghe, P; Van De Broek, Dr; Govaert, P (Journal of Nepal Paediatric Society, 2016)
A one day old Moroccan boy was admitted to our neonatal unit with a giant tuberous right abdominal haemangioma. The clinical examination revealed no other vascular tumours. There was no evidence of heart failure. Ultrasound and MRA documented a giant vascular structure suggestive of haemangioma. The tumor responded well to propranolol treatment. J Nepal Paediatr Soc 2015;35(2):189-191